The Spherical Shock Factor Theory of a FSP with an Underwater Added Structure - Guo Jun (Shock and Vibration, 2019)
A floating shock platform (FSP) is important experimental equipment for the antishock assessment of large-scale shipborne equipment. Generally speaking, the FSP is a square barge structure with a flat bottom. In order to satisfy the key index of the horizontal-to-vertical ratio of the impact environment, a special added structure is mounted to the bottom of the platform, and the impact environment is more complicated due to the added structure. Therefore, the spherical shock factor theory is proposed to analyze the impact environment, and the validity of the theory is proved by numerical experiments. The results show that the average impact spectrum response of the platform is essentially consistent under the same shock factor. Meanwhile, the spherical shock factor builds a linear relationship between the input parameters and structural response, which is convenient for the prediction of impact response.